ANALISIS IMPLEMENTASI TOTAL QUALITY MANAGEMENT TERHADAP KUALITAS LAYANAN PADA SMK BHAKTI ANINDYA KOTA TANGERANG - Sutrisno, Gono; Umiyati, Hesti; Ristiani, Risa (Jurnal Penelitian Manajemen, 2024)
The aim of this research is to analyze the influence of Integrated Quality Management factors on service quality at SMK Bhakti Anindya. Total quality management is a way to continuously improve performance at every level of operation or process, in every functional area of ​​the organization by using human resources. and capital. TQM consists of Quality Assurance (QA) and Quality Improvement (QI), where QA is a company activity that produces documented evidence related to quality, while QI is always associated with programs at various levels of management to achieve better technical and managerial skills in an effort to improve operating methods. and continuous control. Some of the important performances of QI are identifying specific areas of quality improvement and then implementing them into a project, preparing a working group that has the ability to diagnose problems, develop solutions and control them. The research used a sample of 112 educational staff, teachers and students at the SMK Bhakti Anindya. For this reason, the author using SPSS analysis using a questionnaire that was distributed to the students. After going through a trial questionnaire which has been tested for validity and reliability, a regression of the relationship between incentives and company policy on work productivity is obtained, namely through the equation Y = 5.71 + 0.103 + 2.343, which means that every 1 increase in the score of the integrated quality management variable (X1) will affects the increase in the work productivity variable (Y) by 0.428 and every 1 increase in the score of the education and training variable n(X2) will affect the increase in the service quality variable (Y) by 2.34.